Wet pulverization combined with temperature cycling strategy for extraction of Stropharia rugosoannulata protein with attenuating hepatic steatosis on obese mice - Peng Liu; Chen Gao; Wen Li; Wanchao Chen; Zhong Zhang; Di Wu; Tingzhao Li; Shuai Sun; Yan Yang (Food Chemistry: X)
Stropharia rugosoannulata is an edible fungus with high protein content and excellent bioactivities. However, the effective extraction of S. rugosoannulata protein has been a challenge, and the amelioration of it against obesity still remain unclear. Herein, S. rugosoannulata protein (SRA) with mainly molecular weight of 15, 40 and 50 kDa, complete amino acid composition and typical α-helix structure, was obtained by wet pulverization combined with temperature cycling strategy. SRA alleviated the pathological progression in obese mice induced by high-fat diet via regulating lipid metabolism in liver and adipose tissues. SRA could obviously improve hepatic steatosis, which may be attributed to inhibiting MAPK/PGC-1α pathway. Moreover, SRA repaired the cross-talk between gut microbiota and liver via modulating intestinal microecology, and restoring the integrity and function of the intestinal barrier in obese mice. This study highlights an efficient and easy strategy for preparing S. rugosoannulata protein and its effects against obesity.